2012
DOI: 10.1021/ol203268t
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Conformational Analogues of (+)-Peloruside A

Abstract: An efficient synthetic strategy for rapid access to analogues of peloruside A has been demonstrated. The synthetic route was highlighted by a simple esterification-based fragment coupling and a late stage ring-closing metathesis reaction. This convergent route has provided access to rationally designed analogues inspired by the solution conformational preferences of peloruside A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In 2010, Altmann et al [164] reported the stereoselective synthesis of monocyclic peloruside A analog and discovered that the compound is several-hundred-fold less potent than peloruside A in three human cancer cell lines. In 2012, Taylor et al [165] synthesized a set of conformational analogs of peloruside A just in 18 steps from commercial materials by a simple esterification-based fragments coupling and a late stage RCM reaction. This efficient synthetic strategy is significant for the further research, though they didn't make activity evaluation of conformational peloruside A M A N U S C R I P T…”
Section: Fig 14 Total Synthesis Strategies Of Peloruside Amentioning
confidence: 99%
“…In 2010, Altmann et al [164] reported the stereoselective synthesis of monocyclic peloruside A analog and discovered that the compound is several-hundred-fold less potent than peloruside A in three human cancer cell lines. In 2012, Taylor et al [165] synthesized a set of conformational analogs of peloruside A just in 18 steps from commercial materials by a simple esterification-based fragments coupling and a late stage RCM reaction. This efficient synthetic strategy is significant for the further research, though they didn't make activity evaluation of conformational peloruside A M A N U S C R I P T…”
Section: Fig 14 Total Synthesis Strategies Of Peloruside Amentioning
confidence: 99%
“…Few analogues have been published since 2003 11,12. Among them, conformationally constrained analogues such as natural peloruside C 3 12a or synthetic compound 4 obtained by replacement of the C11 and C13 stereogenic centers with a set of olefinic Z and E isomers12b [compounds ( E )‐ 4 and ( Z )‐ 4 , Figure 1] have been recently characterized. At the same time, a stereoselective synthesis of monocyclic peloruside A analogue 5 has allowed the importance of the pyranose ring in the bicyclic core structure of the macrocycle to be outlined (Figure 1, IC 50 = 16.4 μ M on A549 cells) 13…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies with these compounds have centered on determining their mode of action and molecular interactions with tubulin 4 there’s been little focus on understanding their conformational behavior in solution, which we believe is crucial in the process of designing bioactive analogues. 9 Herein, we report the conformational analysis of zampanolide and dactylolide’s shared macrolide core.…”
mentioning
confidence: 99%